Xenobiotic resistance in mosquito eggs: current understanding and data gaps - Turaga, Uday; Peper, Steven T.; Garcia, Carlos J.; Presley, Steven M. (PeerJ, 2025)
Of all mosquito life stages, the egg continues to be the least understood and most vulnerable relative to exposure to external environmental stressors. The propensity of mosquitoes to lay eggs in or near aquatic environments exposes them to a variety of xenobiotic compounds. Owing to their increased use, two xenobiotics, antibiotics and insecticides are increasingly being detected in aquatic ecosystems. Both antibiotics and insecticides are known for their ovicidal effects. Prior to the formation of the serosal cuticle, mosquito eggs are potentially exposed to antibiotics and insecticides due to the permeability of the egg membrane. This short review attempts to summarize the current understanding and to identify the data gaps pertaining to the exposure of mosquito eggs to xenobiotics. The role of male mosquitoes in the propagation of xenobiotic resistance, something that’s been sparsely studied, is also discussed. Additionally, we address the implications of these data gaps relative to the overall objectives of vector control and public health.
Keywords: Mosquitoes; Xenobiotics; Antibiotics; Insecticides; Serosal cuticle